Effect of phosphorus, potassium, and chloride nutrition on cold tolerance of winter canola (Brassica napus L.). (2nd July 2016) - Evans, M. A.; Skinner, D. Z.; Koenig, R. T.; Hulbert, S. H.; Pan, W. L.
ABSTRACT: Winter varieties of canola ( Brassica napus L.) are susceptible to winterkill. Measurements of photosynthetic efficiency and survival of field-grown canola were used to evaluate the effect of chloride (Cl), potassium (K), and phosphorus (P) nutrition on winter field survival in northwestern USA. In a growth chamber experiment, effects of calcium chloride (CaCl2 ), potassium chloride (KCl), ammonium chloride (NH4 Cl), or sodium chloride (NaCl) on the ability to tolerate subfreezing temperatures were evaluated. In the field, overwinter survival was higher, and greater photosynthetic activity continued later into the autumn in plants with increased sap Cl concentrations. In the greenhouse experiment, significantly greater survival occurred in plants with higher sap Cl concentrations, but only in plants that had not been cold acclimated. These results suggested that a greater concentration of chloride ion in the sap of canola plants is related to an increased ability to tolerate subfreezing temperatures, but other processes resulting from cold acclimation may largely obscure this effect.